Komunikasi Dinas Perpustakaan dan Dinas Pariwisata dalam Menyelamatkan Naskah Kuno Surau Latiah Kota Solok - Sevri Pebriona; Emeraldy Chatra; Ernita Arif (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This study discusses the communication carried out by the Library Service and the Tourism Office which were carried out at the same time, with the same goal, namely saving the ancient manuscripts of surau Latiah in Solok City, and not knowing each other that there was a multiplicity of activities. The purpose of the article is to find out the communication experiences and the most meaningful concepts from the communication experiences of the two agencies. The research method is a qualitative Husserl phenomenological approach with a constructivism paradigm. Data obtained from observations, in-depth interviews and documentation. The results of the study show that the communication experience carried out by the two agencies is different. The most meaningful concept from the communication experience of the two agencies is effective communication in the form of persuasive communication that is influenced by other people who are considered important and carried out by means of verbal and non-verbal communication so that there is a change in the attitude of the owner of the manuscript so that he wants to submit the ancient manuscript of Surau Latiah.